(untitled) (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2025)
Effective local government administration is pivotal for grassroots development, yet administrative skills deficits often undermine service delivery in Nigeria. This study measures administrative skills among local government personnel in Cross River State, Nigeria, focusing on leadership, communication, financial management, and ICT proficiency. Employing a descriptive survey design, data were collected through the Administrative Skills Assessment Questionnaire (ASAQ) from 250 local government employees across five local government areas (LGAs) in Cross River State. The sample comprised administrators, clerks, and technical staff, with 60% male and 40% female participants. Findings reveal that 68% of respondents demonstrated moderate leadership skills, while only 45% were proficient in ICT. Financial management skills were notably weak, with 55% scoring below average due to limited training. Key barriers include inadequate professional development (78%) and resource constraints (65%). Rural LGAs reported lower skill levels compared to urban areas (t = 3.87, p < 0.05). The study underscores the need for targeted capacity-building programs to enhance administrative efficiency. Recommendations include regular training workshops, ICT integration, and partnerships with educational institutions to bolster skills. By addressing these gaps, local governments in Cross River State can improve governance and service delivery, fostering sustainable development.